Dynamics Between Malaysian Equity Market And Macroeconomic Variables: An Application Of Kalman Filter Model With Heteroskedastic Error - Cheah, Lee Hen (2006)
Ever since the pioneering work of Kalman and Bucy (1960), Kalman filter model has become widely used in the space programme and control engineering. However,its applications in financial time series have been very few and far in between. Kalman filtering is a set of equations which allows an estimator to be updated once a new observation becomes available. A model for the monthly Kuala Lumpur Composite Index from April 1986 to February 2005 is proposed and investigated. The model allows the mean reversion level of Kuala Lumpur Composite Index to be modeled stochastically.